2023
DOI: 10.33137/ijidi.v7i3/4.40292
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Power, and Social Inclusion: Afghan Refugee Women’s Interaction with ICT in Germany

Laura Schelenz

Abstract: Afghan refugee women settle in Germany to escape persecution by militant groups and social marginalization in Afghanistan, among other things. They face challenges in Germany, such as language barriers, demanding bureaucratic requirements from German administrations, and discrimination. Academic and public discourses promote the information and communication technologies (ICT)-enabled social inclusion of refugees into the host society. ICT is widely seen as an essential tool to support refugees. Against this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Costa (2018) described how one user in her ethnographic fieldwork used social media "to conceal and display different aspects of himself to different audiences" (p. 3645). While "previous research has suggested that anonymity in online settings is likely to encourage verbal attacks and insults" (Maia & Rezende, 2016, p. 124, emphasis added), our focus here is not the anonymity of social media platforms, per se, but the platforms that afford private communication, 3 such as WhatsApp and Snap (Schelenz, 2023;Trauthig & Woolley, 2023). With these social media platforms, one can communicate with friends and family in a private, one-to-few manner.…”
Section: Affordancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa (2018) described how one user in her ethnographic fieldwork used social media "to conceal and display different aspects of himself to different audiences" (p. 3645). While "previous research has suggested that anonymity in online settings is likely to encourage verbal attacks and insults" (Maia & Rezende, 2016, p. 124, emphasis added), our focus here is not the anonymity of social media platforms, per se, but the platforms that afford private communication, 3 such as WhatsApp and Snap (Schelenz, 2023;Trauthig & Woolley, 2023). With these social media platforms, one can communicate with friends and family in a private, one-to-few manner.…”
Section: Affordancesmentioning
confidence: 99%
“…For example, geographically isolated Queer individuals have been able to connect with other members of the Queer community (Craig et al, 2021;Hanckel et al, 2019). Many individuals report that connecting with family is a significant factor in their use of social media (Schelenz, 2023;Whiting & Williams, 2013). Similarly, Russian-speaking immigrants in Finland maintained connections with their homeland via social media (Khvorostianov et al, 2012;Mallapragada, 2006;Mitra, 2001;Vorobeva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%